Pharmacokinetics and Biodistribution Study of Paclitaxel Liposome in Sprague-Dawley Rats and Beagle Dogs by Liquid Chromatography-Tandem Mass Spectrometry - Wang, X.; Song, L.; Li, N.; Qiu, Z.; Zhou, S.; Li, C.; Zhao, J.; Song, H.; Chen, X. (Drug Research, 2013)
Lipusu is the first paclitaxel liposome preparation approved in the world and has been widely used in China for the treatment of ovary, breast and non-small cell lung cancer. In present study we evaluated the pharmacokinetic and tissue distribution characteristics of paclitaxel liposome in Sprague-Dawley rats and Beagle dogs. A rapid and simple liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay was developed for the determination of paclitaxel in plasma and tissues. The plasma concentrations of paclitaxel in both rats and dogs initially declined steeply, followed by slow elimination after intravenous administration of Lipusu at 5 mg/kg and 1 mg/kg, respectively. The pharmacokinetic parameters calculated by a non-compartmental method in rats and dogs were as follows: AUC0–24: 3 566.5±1 366.1 and 443.2±165.7 μg · h/L, CL: 1.5±0.5 and 2.1±0.6 L/h/kg, Vd: 20.0±7.8 and 38.4±12.5 L/kg, t1/2: 9.3±2.9 and 14.1±6.9 h, respectively. Biodistribution results in rats showed that except for brain and testis, liposomal paclitaxel was extensively distributed into various tissues, especially highly in liver and spleen.
Keywords: lipusu; disposition; in vivo; LC-MS/MS